2019
DOI: 10.1002/pbc.27728
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐specific differences in parental health‐related quality of life in childhood cancer

Abstract: Background Parents of children with cancer are at risk for impaired health‐related quality of life (HRQoL). Most prior research has focused on the HRQoL of mothers. The aim of this study is to describe HRQoL in mothers and fathers, and determine the influence of sociodemographic, medical, and psychosocial factors. Procedure In a cross‐sectional study, both parents completed questionnaires on sociodemographics, distress, and HRQoL. Parental HRQoL was compared to healthy population values. Differences between mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 53 publications
1
43
0
4
Order By: Relevance
“…Furthermore, we did not have information on which parent was the primary caregiver; perhaps we would have found that this parent's rating was consequently higher or lower than the second parent's rating. However, we do not really expect this, since the mother is still the primary caregiver in the majority of the Dutch families [14]. Finally, it would have been interesting to include child self-reports as well, and to take these into account in the comparison of parental proxy ratings.…”
Section: Limitationsmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, we did not have information on which parent was the primary caregiver; perhaps we would have found that this parent's rating was consequently higher or lower than the second parent's rating. However, we do not really expect this, since the mother is still the primary caregiver in the majority of the Dutch families [14]. Finally, it would have been interesting to include child self-reports as well, and to take these into account in the comparison of parental proxy ratings.…”
Section: Limitationsmentioning
confidence: 97%
“…Data of this study are derived from the "Amsterdam Parent Project", a cross-sectional multicenter study on parental sleep, QoL and psychosocial functioning in childhood cancer. A detailed description of the Amsterdam Parent Project is given elsewhere [14]. For the purposes of the current study, the questionnaires on parent-rated child HRQoL as well as those on parental QoL and distress were included.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, it is known that parents of pediatric cancer patients are at risk for impaired QoL, both during and after treatment, and that major determinants of adverse QoL outcomes are sleep problems and distress 12–17 . Specifically during ALL maintenance treatment, reports on parental psychosocial functioning are sparse, but they show high prevalence of sleep disturbances and significant emotional distress 18–23 …”
Section: Introductionmentioning
confidence: 99%